The Effect of Reproductive Health Gymnastics on Hemoglobin Levels of Female Adolescents (Medico Legal Update, 2020)
Female adolescents who have experienced menstruation are at high risk of anemia, especially iron nutritionalanemia. Efforts made by the Government in overcoming anemia in adolescent girls are by providing BloodPlus Tablets, but based on data from the Ministry of Health in 2017, the percentage of Fe (iron) tabletsobtained by adolescent girls is still very low, namely 13.8%, so it is not yet fulfilling. the national targetis 30%, so there needs to be another strategy to overcome anemia in adolescent girls. Reproductive healthexercise is one of the physical activities that can be an alternative for adolescent girls who experienceanemia because it can increase hemoglobin production. This study analyzed the hemoglobin levels ofadolescent girls after being given reproductive health exercises. The results showed that Kespro exercisehad an effect on hemoglobin levels in adolescent girls with a p value